Towards Value-Based Healthcare and the Role of Regional Agencies: the Approach of the Veneto Region - Rosanna I Comoretto; Teresa Gasparetto; Erica Tavazzi; Dario Gregori (Epidemiology, Biostatistics and Public Health)
No Abstract